The Fallopian Tube: Primary Site of Most Pelvic High-grade Serous Carcinomas. Issue 1 (1st January 2009) - Salvador, Shannon; Gilks, Blake; Köbel, Martin; Huntsman, David; Rosen, Barry; Miller, Dianne
Abstract : Epithelial ovarian cancer is the most common cause of mortality from gynecologic malignancy, and most of epithelial cancers are of serous type. The site of origin of pelvic high-grade serous carcinoma has been the subject of debate for 60 years. This paper reviews the evidence that pelvic serous carcinoma originates from the fallopian tube mucosa and puts forward a theory that inflammation in the tube, caused by menstrual cytokines or infection, is critical to the genesis of these tumors. Other risk factors for pelvic serous carcinoma will be reviewed, including oral contraceptive use, parity, infertility, and tubal ligation. Studies were identified for this review by searching the English language literature in the MEDLINE database between the years 1995 and 2007 using the following keywords: fallopian tube neoplasia, ovarian serous adenocarcinoma, pregnancy, oral contraceptive, infertility, pelvic inflammatory disease, cytokines, menstruation, and tubal ligation, followed by an extensive review of bibliographies from articles found through the search. The clinical implications of this theory are discussed, and a change in surgical practice is recommended, with salpingectomy at the time of simple hysterectomy. This theory also has implications for the development of new methods of screening for pelvic serous carcinomas, as there are no screening methods that are currently available to find this form of cancer in an early stage. Inflammatory markers could be detected in the vagina from the fallopian tube indicating possible chronic inflammation and a risk factor for mutagenesis leading to serous carcinoma.